The Unnaming of Aliass - Bolender, Karin (punctum books, 2020)
The Unnaming of Aliass performs a paradoxical quest for wildly "untold" stories in the company of one special donkey companion, a femammal of the species Equus asinus and, significantly, a registered "American Spotted Ass." Beast of burden that she is, this inscrutable companion helped carry a ridiculous load of human longings and quandaries into a maze of hot, harrowing miles, across the US South from Mississippi to Virginia, in the summer of 2002 -- all the while carrying her own onerous and unreckoned burdens and histories. Over two decades, the original journey evolved -- from the cracking-open of a quasi-Western novel-that-never-was by an implosive pun, into an ongoing philosophical and assthetic adventure: a hybrid roadside- and barnyard-based living-art practice, wherein "Aliass" un/names something much harder to grasp than the body of a lovely little ass: protagonist, setting, and traditional Western narratives turn inside-out around this "name-that-ain't." Through a deeply dug-in questioning of its own authorial assumptions, The Unnaming of Aliass makes space for untold autobiographies and bright dusty lacunae, tracing ineffable tales through the tangled shapes and shadows that interweave in any environment.